2016
DOI: 10.1159/000447873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Outcomes of In Vitro Fertilization/Intracytoplasmic Sperm Injection Among Polycystic Ovarian Syndrome Patients

Abstract: Background: The aim of this study is to assess the effect of body mass index (BMI) on outcomes of in vitro fertilization (IVF) / intracytoplasmic sperm injection (ICSI) among polycystic ovarian syndrome (PCOS) and non-PCOS patients. Methods: This was a retrospective cohort study that was performed in the Second Hospital of Hebei Medical University. Patients who were under 35 years old were included in the study and were divided into four groups based on their BMI. The number of retrieved oocytes, implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 58 publications
1
45
2
1
Order By: Relevance
“…NO is an important factor determining IVF success rates [59]. The report is of utmost importance as a recent study has reported that the IVF success rates in obese PCOS women is low on account of higher miscarriage risk [1]. Hence, NOx insufficiency in PCOS women has to be addressed at an early level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO is an important factor determining IVF success rates [59]. The report is of utmost importance as a recent study has reported that the IVF success rates in obese PCOS women is low on account of higher miscarriage risk [1]. Hence, NOx insufficiency in PCOS women has to be addressed at an early level.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is ranked as the most common cause of female infertility on a global scale. Further deteriorating the scenario PCOS patients have low IVF/ICSI success rates [1] and high incidence of ovarian hyperstimulation syndrome (OHSS) [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that changes in serum proteins are related to progesterone in PCOS patients, and progesterone improves ovarian functions by upregulating EREG, inhibin βA, IDE, PDGF-D and KNG1 expression. The accumulated evidences show that PCOS is one of the major causes leading to infertility [1, 36-37]. Based on the complexity of hormone disorders in PCOS patients, such as high estrogen, high androgen, or low progesterone, as well as the combination of the 2 or 3 of the hormones [38], although the clinical treatment strategy now is mainly by anti-estrogen with clomiphene citrate to induce ovulation and anti-androgen with flutamide to alleviate hyperandrogenism, we propose that progesterone supplementation in combination with routine treatments may improve the therapeutic effect in PCOS patients, and prevent the occurrence of abortion and premature delivery, especially patients with low progesterone level.…”
Section: Discussionmentioning
confidence: 99%
“…Lin and Lujan [8] reviewed the diet and exercise of PCOS women and found that there was no significant difference in exercise amount between PCOS women and healthy women, but PCOS women were characterized by high-calorie diet, excessive intake of saturated fatty acid and lack of dietary fiber. After receiving ART assisted pregnancy therapy, the clinical pregnancy rate and live birth rate of obese PCOS women were significantly lower than those of normal weight PCOS patients, and the risk of miscarriage was increased [9,10]. Therefore, it was very important to control BMI in the optimal range before pregnancy assistance to improve the success rate of ART.…”
Section: Exercise or Combination With Other Methods Improve Reproductmentioning
confidence: 99%